Kepraktisan Buku Ajar Perencanaan Pembelajaran Anak Usia Dini Berbasis Terapan Nilai Islam - Nasution, Raisah Armayanti (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
Teaching materials are an important component in learning that must be studied, arranged and scrutinized so that they become a source of learning material. However, the problem is the lack of availability of teaching materials, in this case textbooks related to early childhood learning planning based on Islamic values in the PIAUD Study Program at UIN North Sumatra, Medan. So this research aims to test the practicality of learning planning textbooks based on the application of Islamic values in early childhood. This research is part of Research and Development (R&D) research using the EDDIE method. The subjects of this research were 28 students and 3 lecturers. Data collection techniques in this research are observation and questionnaires. This research analyzes learning planning textbooks based on the application of Islamic values to early childhood. The development of an early childhood learning planning textbook discusses early childhood learning planning based on Islamic values which is adapted to the applicable curriculum. After being tested for feasibility, furthermore the practicality test was tested with the results of the practicality test by students, the percentage result was 89.47% categorized as very practical and the results of the practicality test on lecturers obtained an average of 87%, categorized as very practical, meaning the textbook product was practically used.